Menstrual Hygiene Management Education to Improve Knowledge and Attitudes of Elementary and Secondary School Students in Semarang City - Sutopo Patria Jati; Nurhasmadiar Nandini; Erlin Friska; Vanessa Rizky Aditya; Nadiya Ridha Afifah (Journal of Public Health for Tropical and Coastal Region, 2026)
Introduction: Inadequate Menstrual Hygiene Management (MHM) among adolescents, driven by cultural stigma and limited access to accurate information, increases risks of reproductive tract infections and social challenges like school absenteeism in urban settings like Semarang City, Indonesia. This study evaluates the effectiveness of a quiz card game intervention in enhancing MHM knowledge and attitudes among 1,234 adolescents aged 9–15 years from 19 elementary and junior high schools. Methods: Using a pre-experimental, one-group pretest-posttest design, structured questionnaires assessed baseline and post-intervention knowledge and attitudes. The 30-minute quiz card game sessions, facilitated by trained educators, incorporated visual aids to address MHM practices and cultural misconceptions. Results: The Wilcoxon Signed-Rank Test showed significant improvements in knowledge (Z = -14.874, p < 0.001; mean: 5.08 to 6.67) and attitudes (Z = -12.851, p < 0.001; mean: 29.41 to 31.64), with 63% of respondents (777 individuals) demonstrating increased knowledge scores, including 336 with initially poor knowledge. Conclusion: These findings underscore the quiz card game’s efficacy in engaging adolescents and reducing stigma. Integrating such interactive, culturally sensitive tools into school curricula can promote healthy menstrual practices, mitigate health risks, and empower adolescents in Semarang to adopt dignified hygiene behaviors early.